Evaluating the Land Subdivision of Residential and commercial Lands in terms of Land Subdivision Indicators and Land Stakeholders Case study: District 1 and 3 of Tabriz City - Akbar Asghari Zamani; Shahrivar Rostaei; Mohammad Ali Koushesh Vatan (نشریه جغرافیا و برنامه‌ریزی, 2021)
Introduction Land use planning, especially land subdivision, plays a key role in making a decision on how to properly use the land and subdivide it. That is why such planning influences the state of the environment and can have positive and negative effects (Metternicht, 2018: 3). In simple words, with different street network patterns, land subdivision creates various lots in different shapes and with various advantages. In other words, at the execution stage, land subdivision affects the land price. So, some lots will have a higher value due to their advantages compared to some other lots (Evans, 2004: 75). Considering what abovementioned, this comparative study aims: 1 – To evaluate the quality of the existing land subdivisions in the planned texture, worn-out texture, and informal settlements using the current land subdivision standards; 2 – To assess the correlation between the opinions of experts, real estate agents, property owners, and non-owners on the quality of land subdivision with the current status of the land subdivision based on research indicators; 3 – To evaluate the impact of human-managerial factors and the land value in the land subdivision process. Data and Method To collect data, a field study was used. To select blocks randomly as research sample, the Fishnet tool in ArcMap software was used. Totally, 353 blocks in district one and 386 blocks in district three were selected as research samples. To collect data on the status of the land subdivision in the selected blocks, a database was constructed for the study areas using the indicators of area, number of frontages, building orientation, chamfer or fillet, street width, street function, lot shape, aspect ratio, and distance to different land-uses, then the required analyses were performed. In the next step, using a researcher-made questionnaire, the three groups of experts, real estate agents and property owners, and non-owners were surveyed to align the observed advantages and disadvantages with the opinions of the three abovementioned groups. The validity of the questions was estimated using face validity. Its Cronbach's alpha coefficient was obtained 0.76, which was within the acceptable range. The statistical population included the total population of the two studied districts (n=448,121 people) and the sample size was estimated to be 384 people using the Cochran formula at 95% confidence level and with a 5% error. Also, SPSS software was used for questionnaire analysis.   Results and Discussion According to the analysis carried out for the first aim, the obtained averages revealed the inappropriate residential and commercial subdivisions. In this issue, streets play a very important role, because different street network patterns significantly affect the characteristics of lots. As observed,  for residential and commercial land-uses in both districts, the average width of the streets and the adaptation level of land-uses with the street function were below the standards, which also reduced the quality of access. According to the analysis performed for the second aim, it was found that experts' opinions on six cases in district one and seven cases in district three were significantly correlated with the current status of the land subdivision. Also, property owners and non-owners on five cases in district three and two cases in district one were significantly correlated with the current status of the land subdivision. Real estate agents' opinions on one case in each district were significantly correlated with the current status of the land subdivision. For the third aim, it was found that the respondents in district one and district three considered the land value and human-managerial factors as effective factors in inappropriate land subdivisions, respectively. In other words, it can be said that the land value and human-managerial factors, along with the lack of efficient solutions and proper surveillance of land subdivision, are considered as factors for inappropriate land subdivision in the study area. In addition, with an average of 3.5 in district one, experts and real-estate agents have assessed the land value more effective in inappropriate land subdivisions compared to the property owners and non-owners. Also, with an average of 3.7 in district three, experts and property owners and none property owners have assessed the human-managerial factors more effective in inappropriate land subdivisions compared to the real estate agents. Conclusion Findings showed that according to the land subdivision indicators used in our research, residential and commercial land-uses don’t meet the land subdivision standards. In this case, streets play the more dominant role than other factors. Measuring the alignment of experts, real estate agents, property owners and non-owners' opinions on the quality of land subdivision with its current status based on research indicators showed that with the highest frequency, experts' opinions on six cases in district one and seven cases in district three are significantly correlated with the current status of the land subdivision. Finally, according to the three abovementioned groups' opinions, the land value in district one and the human-managerial factors in district three were evaluated as effective factors in inappropriate land subdivisions.